Pengembangan Ekonomi Kreatif dan Keragaman Budaya dalam Perspektif Antropologi - Suciyadi Ramdhani (Empower : Jurnal Pengembangan Masyarakat Islam, 2020)
This article aims to explain the contribution of creative economic development in the effort to lift local cultural diversity in Indonesia, which is examined in the perspective of anthropology. Through a two-month literature study, The authors found that the development of the creative economy at least resulted in two implications of reducing community economic gaps and efforts to foster cultural work in Indonesia. The first implications show that according to the survei of Badan Pusat Statistik (BPS) and Badan Ekonomi Kreatif (Bekraf), the contribution of creative economy to the country's income are large and increase continuously. The second implication shows that the potential to explore cultural diversity in Indonesia is one of them by developing a distinctive cultural product that is locally characterized. In anthropology perspective, culture and creative economy have a correlation which both come from an infinite human idea. Through ideas, both finds their base in converting social capital into economic capital and vice versa